PENGEMBANGAN BAHAN AJAR FLIPBOOK BERBASIS HEYZINE MATERI GAYA KELAS IV SD - Rahayu, Suci Indah; Kartono, Kartono; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This research aims to develop a practical flipbook learning resource for the IPAS (Science and Social Studies) subject on the topic "Forces Around Us" for elementary school students. The approach used in this research is Research and Development (RD) with the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection was conducted through a qualitative approach, including interviews and expert assessments of the product, as well as a quantitative approach using expert feasibility evaluations and student responses. The research findings showed that the design aspect of the flipbook received a score of 82% categorized as "Feasible". The material aspect scored 88,33%, and media aspect scored 87,91%, both categorized as "Very Feasible". Student evaluations of the flipbook showed an average score of 88,28%, categorized as "Very Good". These findings suggest that the flipbook is effective and meets the criteria as an engaging and informative learning medium. Based on these results, it can be concluded that the developed flipbook is suitable for use as a learning resource in IPAS activities at the elementary school level and can enhance students understanding of scientific concepts related to forces.